2011
DOI: 10.1371/journal.pone.0026633
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intrinsically Disordered Prostate Associated Gene (PAGE5) at Single Residue Resolution by NMR Spectroscopy

Abstract: BackgroundThe Cancer-Testis antigens (CTA) are proteins expressed in human germ line and certain cancer cells. CTAs form a large gene family, representing 10% of X-chromosomal genes. They have high potential for cancer-specific immunotherapy. However, their biological functions are currently unknown. Prostate associated genes (PAGE) are characterized as CTAs. PAGE5 is one of six proteins belonging to this protein family, also called CT16.Methodology/Principal findingsIn this study we show, using bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Comparison with Other PAGE Family Members-The only other cancer/testis antigen studied in detail using biophysical methods is PAGE5 (29). However, the role of posttranslational modifications in PAGE5 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with Other PAGE Family Members-The only other cancer/testis antigen studied in detail using biophysical methods is PAGE5 (29). However, the role of posttranslational modifications in PAGE5 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Transient ␤-extended and helical structures are represented by arrows and cylinders, respectively. PAGE5 preferences from an earlier study (29) are shown in white at the bottom of the alignment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A). The spectrum shows poorly dispersed crosspeaks, with the proton chemical shifts ranging from 7.5 to 8.5 1 H ppm, indicating that A2A-ct undergoes fast conformational dynamics in solution, which is typical for highly disordered proteins (69). The conformational heterogeneity of intrinsically disordered proteins calls for special means for the NMR signal assignment.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…NMR spectroscopy can be employed to study structural features of disordered proteins at single-residue resolution (69). To confirm the disordered nature of A2A-ctL in solution, we measured a two-dimensional 1 H, 15 N-HSQC spectrum of A2A-ctL at 800 MHz 1 H frequency (Fig.…”
Section: Nmr Spectroscopymentioning
confidence: 99%